G. Chueca, Ángel; Gutiérrez Castillo, Victor Luís; Irene Blázquez Rodriguez (coords.) (2009): Las migraciones internacionales en Mediterráneo y Unión Europea, Barcelona, Huygens Editorial - Ospina Sánchez, Gloria Inés (UNISCI Discussion Papers, 2010)
Sin resumen